DAYA PSIKOLOGIS MAHASISWA S1 UNIVERSITAS PENDIDIKAN INDONESIA - Dahlan, Tina Hayati (PEDAGOGIA, 2015)
Writing this article aims to describe the empirical data on student psychological power S1 UPI that includes psychological problems in fulfilling the needs and competencies of intrapersonal and interpersonal competence as elements that build psychological power. This study was conducted in 2011 using quantitative descriptive method to sample as many as 585 students S1 UPI selected using non probability sampling techniques. The results showed that at the university level andfaculty, the highest percentage in the fulfillment of psychological problems is not free in the choice of life and does not understand the responsibilities attached to the selection. Psychological power level students in general are in a category average, the percentage of students who have psychological power below the average higher than the above average, as well as the distribution of competence intrapersonal and interpersonal competence. The percentage of students FPBS and FPMIPA with power levels of psychological, interpersonal competence, and interpersonal competencies under average considerably higher than students with psychological power levels above the average; while the percentage of students FIP and FPTK with power levels of psychological, interpersonal competence and interpersonal competence above average muchhigher than students with psychological power levels below average.Keywords: psychological power, psychological, interpersonal competence, interpersonalcompetence.